Maximizing Banana Production through Effective Bunch Covering: A Review - Meher, Durgadatta; Subba, Susan; Mondal, Debasmita; Ghosh, Swapnamay (NG Agricultural Sciences, 2025)
India is the largest producer of bananas globally, as it produces almost 18% of the world's production, which is approximately 139 million metric tons. Even so, Indian banana exports are minimal due to several reasons. The outward looks and quality of bananas, both externally and internally, depending on their market value and internal properties, are influenced by several factors, such as practices in farming. The use of banana bunch covers provides physical protection that enhances appearance by maximally pigmentation of the skin and reduction of blemishes. The practice also affects the micro-environment for fruit growth, having several positive effects on internal quality. Bunch covers have also been observed to decrease the likelihood of diseases, insect infestation, mechanical damage, sunburn, cracking, agrochemical residues, and bird pecking. Although bunch covering is a time-consuming process, an evaluation of its cost-effectiveness is required for the promotion of its use on a worldwide scale. Few studies have analyzed the impact of banana bunch covers on different regions, and findings are not available in a systematic manner.